A Study of Endoscopic and Clinical Profile of Dyspepsia in Afghan Momand Medical Complex & Research Center, Eastern Region, Nangarhar, Afghanistan - Haqmal, Ziaulhaq; Zaheer, Ismatullah (Journal of Cardiology and Cardiovascular Medicine, 2025)
Dyspepsia refers to acute, chronic, or recurrent pain or discomfort centered in the upper abdomen. An international committee of clinical investigators (Rome III Committee) has defined Dyspepsia as Epigastric pain or Burning, early satiety, or postprandial fullness Dyspepsia occurs in 15 % of the Adult population and accounts for 3% of general medical office visits. The descriptive study was carried out in Eastern Afghanistan, Afghan Momand Medical Complex & Research Center, Department of Gastroenterology, during the years 2023-2024. To know the Clinico-Endoscopy of Dyspepsia, for patients who present with investigated Dyspepsia to Gastroenterological OPD & IPD. The study result showed, there were a total of patients 467, and of these patients 230 were Male and 237 were Female. According to the Age, 45 patients were under Age < 20, 219 patients were between the ages 21-40 years, 130 patients were between ages 41-60 years and 73 patients were over 60 years of Age. However according to the presentation, 357 patients had Dyspepsia, 59 patients had Dysphagia, 13 patients had Chronic Liver Diseases & Screened for Varices, 3 patients presented after Acid ingestion, 2 patients had Anemia, 11 patients had persistent vomiting and 22 patients had suspected GI-Bleeding. Furthermore in Esophageal findings from a total of 467 patients 34 patients had Esophageal Candidacies, 6 patients had Esophageal Narrowing, 25 patients had Esophageal Growth, 71 patients had Hiatus Hernia, 180 patients had LA Grade A Esophagitis, 21 patients had LA Grade B Esophagitis, 6 patients had LA Grade C Esophagitis, 3 patient had LA Grade D Esophagitis. 16 patients had Lax Lower Esophageal Sphincter, 9 Patients had High-Risk Esophageal Varices, 3 patients had Small Esophageal Varices and 150 patients had Normal Esophagus and in Gastric findings from total all above patients, 4 patients had Antral Gastritis, 50 patients had Corpus Gastritis, 1 patient had Fundal Gastritis, 4 patients had Nodular Gastritis, 199 patients had Pan-Gastritis, 108 patients have Severe Pan Erosive Gastritis, 23 patient had Gastric Erosions, 6 patients had PHG (Portal Hypertensive Gastropathy), 3 Patients had Fundal Varices, 5 patients had Gastric Polyps, 5 patients had Gastric Growth, 2 patients had Pyloric Stenosis, 8 patients stomach not seen due to Esophageal Growth, 67 patients stomach were normal. In the present study there were Duodenal findings from a total of the above patients 48 had Duodenitis, 2 patients had Duodenal Polyps, 2 patients had duodenal ulcers, 1 patient had Duodenopathy, 2 patients had Duodenopathy, 2 patients Duodenum not seen due to Pyloric Stenosis and 413 patients Duodenum were normal. Regarding the habits in our study in which a total of 467 patients were examined 135 of the above patients had snuff habits, 103 patients had smoking habits, 2 patients were Heroin addicts and 227 of the total patients didn’t have any habits (the majority of them were using spicy food, overfeeding, drinking of nonalcoholic beverages, fatty foods, NSAIDs ...) and the higher incidence of Dyspepsia was in Female patients, Also with the age between 21-40 years (43%) patients, Also the higher incidence of Dysphagia 47% were in patients with Age >60 years, the Endoscopy showed that 83% patients had Gastritis also higher incidence regarding the habits 29% had snuff habit and 22% had a smoking habit.